2014
DOI: 10.1093/brain/awu221
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific impairment in metacognitive accuracy following anterior prefrontal lesions

Abstract: Convergent evidence supports a role for anterior prefrontal cortex (PFC) in metacognition—the capacity to evaluate cognitive processes—but whether metacognition relies on global or domain-specific substrates is unknown. Fleming et al. report that patients with anterior PFC lesions show impaired perceptual metacognition despite intact memory metacognition, supporting a domain-specific account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
324
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(370 citation statements)
references
References 83 publications
(137 reference statements)
18
324
2
3
Order By: Relevance
“…Arguably, the applied task may not have tapped into the full content of the Presence Module, which also encompassed interoception and metacognitive awareness (44). Monitoring and metaawareness-related processing could be in line with thickening in the medial PFC, a region suggested by cross-sectional studies to participate in these functions (66)(67)(68).…”
Section: Discussionmentioning
confidence: 71%
“…Arguably, the applied task may not have tapped into the full content of the Presence Module, which also encompassed interoception and metacognitive awareness (44). Monitoring and metaawareness-related processing could be in line with thickening in the medial PFC, a region suggested by cross-sectional studies to participate in these functions (66)(67)(68).…”
Section: Discussionmentioning
confidence: 71%
“…Importantly, the diverse connectivity profile of pgACC is consistent with this area as central to the formation of local and global estimates of probability correct: pgACC is connected to surrounding medial prefrontal cortex, dorsolateral and ventrolateral prefrontal cortex, cingulate cortex, subcortical areas, such as hippocampus and striatum, and posterior areas, including parietal cortex (31). These findings may help explain why metacognition, the ability to monitor and evaluate the success of one's performance, is often impaired after prefrontal lesions and/or degeneration (32)(33)(34)(35). If pgACC is indeed critical for confidence formation, compromising pgACC, or connections to and/or from pgACC, should naturally lead to discrepancies between subjective evaluations and objective performance.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 63%
“…the ability to discriminate correct responses from guesses on a trial-by-trial basis, Baird et al (2013) found no correlation between perceptual and mnemonic tasks (though see McCurdy et al, 2013, for a different result), and Fleming, Ryu, Golfinos, and Blackmon (2014) provided neuropsychological evidence for a dissociation between sensitivity in the two domains. In the present study, although metacognitive sensitivity generalized across the two perceptual tasks, it was unrelated to any measure from the delayed intention task.…”
Section: Domain-specificity Of Metacognitionmentioning
confidence: 98%